2010
DOI: 10.1097/tp.0b013e3181ca7389
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome Changes of Chronic Tubulointerstitial Damage in Early Kidney Transplantation

Abstract: Allografts display predictable immune and fibrotic gene expression profiles, with patterns of expression gradually varying by time after transplantation. The pathology reflects differential activation of intrinsic pathways. Gene expression predated histologic damage, suggesting its possible use in early diagnostic testing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
25
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 31 publications
6
25
0
Order By: Relevance
“…The inverse correlation of injury-up and injury-down changes were first described in mouse kidney isografts and shown to be augmented in allografts, and later in human kidney allograft biopsies for cause and heart transplant biopsies (23,33). Other groups have confirmed this pattern in protocol biopsies (38)(39)(40)(41)(42). This disturbance correlates with the history of DGF and with the extent of inflammation by histopathology and thus with the lesions of TCMR.…”
Section: Discussionsupporting
confidence: 52%
“…The inverse correlation of injury-up and injury-down changes were first described in mouse kidney isografts and shown to be augmented in allografts, and later in human kidney allograft biopsies for cause and heart transplant biopsies (23,33). Other groups have confirmed this pattern in protocol biopsies (38)(39)(40)(41)(42). This disturbance correlates with the history of DGF and with the extent of inflammation by histopathology and thus with the lesions of TCMR.…”
Section: Discussionsupporting
confidence: 52%
“…DEGs unique to CNI biopsies are enriched for gene sets associated with CNIT, fibrosis and CAI Only biopsies from CNI-treated patients showed significant enrichment (p < 0.05) of genes associated with CNIT (identified from the RPTE model; Table 1), published gene sets associated with chronic allograft damage and gene sets generated from unrelated renal allograft biopsies with chronic transplant injury (19). These same CAI and fibrotic gene profiles were not enriched in the biopsy samples from patients treated with belatacept.…”
Section: Resultsmentioning
confidence: 99%
“…Studies of mRNA and miR in kidneys with fibrosis reveal that many molecular changes associated with fibrosis are related to inflammation and matrix remodeling (21)(22)(23)(24)(25). We previously reported that fibrosis in human kidney transplants was associated with transcripts expressed in certain inflammatory cells: mast cell transcripts (MCATs) such as carboxypeptidase 3 (CPA3) (26) and immunoglobulin transcripts (IGTs) representing plasma cells (27).…”
Section: Funding Canada Foundation For Innovation and Genome Canadamentioning
confidence: 99%